General Movements and Outcome in Children with Birthweights ≤ 500 Grams at Age 5 to 6 Years - Rieger-Fackeldey, Esther; Schulz, Peter; Schulze, Andreas (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Background The prognosis of long-term outcome in the delicate subgroup of preterm infants born with a birthweight ≤ 500 g is difficult. We wanted to determine whether general movements (GMs) correlate with outcome at 5 to 6 years of age in preterm children with birthweights ≤500 g.Methods GMs were assessed up to 20 weeks postterm age in a cohort of infants born consecutively in our unit between 1998 until 2003. A structured neurological examination, the Gross Motor Function Classification Scale, and the Kaufman Assessment Battery Test for Children were applied in surviving children at 5 to 6 years. In relation to long-term outcome, only the postterm GM assessment was analysed.Results Of 44 infants in total, 19 received immediate life support in the delivery room and were admitted to the NICU (GA 25 weeks [22.3–29.5]; BW 440 g [334–490]). All 9 surviving infants received GM assessment, but only 8 out of 9 infants had postterm assessment; all 9 had outcome assessment at 5 to 6 years. Children with female sex and birthweights>400 g had better outcomes than those with male sex and birthweights < 400 g. Normal fidgety movements and normal repertoire were associated with normal development at early school age in 3 children, in one child with moderate cognitive impairment and light motor impairment. Pathological fidgety movements or repertoire were associated with abnormal motor development and moderate and severe cognitive impairment in 3 children and with normal development in one child.Conclusion This study shows that normal fidgety movements at postterm age combined with birthweight and sex may predict normal motor and cognitive outcome in extremely preterm children with birthweights ≤500 g.
Keywords: development; extremely low birth weight infant; outcome; general movements